Lesser Kestrel (Falco naumanni) ground prey abundance during its breeding season in central Greece - Christakis, Christos E.; Sfougaris, Athanassios I. (Acta Biologica Szegediensis, 2025)
The Lesser Kestrel (Falco naumanni) is a bird of prey, highly dependent on agricultural landscapes for foraging. This study examines the availability of its prey in different crop types within the Thessalian Plain, central Greece, and assesses how agricultural practices in different cultivations influence prey abundance. Results indicate variations in prey abundance among different crops and study periods. Fallow/ uncultivated fields and legume crops provided the highest prey availability, particularly for key prey groups such as Coleoptera and Orthoptera, making them crucial for Lesser Kestrel foraging. In contrast, intensive crops such as maize and cotton exhibited lower prey abundance, particularly in early growth stages, thus limiting their suitability as foraging habitats. The findings highlight the impact of intensive and extensive agricultural practices on Lesser Kestrel prey populations. Sustainable land management strategies are essential for supporting Lesser Kestrel conservation in agroecosystems.